2015
DOI: 10.1017/ipm.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Irish General Practitioner referrals to psychological therapies

Abstract: ObjectiveGeneral Medical Practitioners play a crucial role in the detection and referral of mental health problems in primary care. This study describes the referral patterns of Irish General Practitioners (GPs) to psychological therapies and profiles the range of psychological therapies available.MethodA 21-item study-specific questionnaire exploring referral processes to psychological therapies was sent to all GPs listed by the Irish College of General Practitioners in one county in Ireland. A 19-item questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
2
1
Order By: Relevance
“…The prevalence of mental health conditions in our study is lower than has been reported in an earlier Irish study (Cullinan et al 2016). Data for this trial were based on GPs' recall, which was measured using a 21-item questionnaire.…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence of mental health conditions in our study is lower than has been reported in an earlier Irish study (Cullinan et al 2016). Data for this trial were based on GPs' recall, which was measured using a 21-item questionnaire.…”
Section: Discussioncontrasting
confidence: 54%
“…Within primary healthcare, general practitioners (GPs) play a significant role in providing support for people experiencing a mental health problem, including facilitating access to psychotropic medications (Cullinan, Veale, & Vitale, ). GPs are the main access point to psychotropic medication and to specialist mental health services (Brunero, Jeon, & Foster, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, patients may lack knowledge about psychotherapy and psychotherapists (Thompson, Bazile, & Akbar, 2004). A study by Cullinan, Veale, and Vitale (2016) showed that GPs also have limited knowledge about specific psychotherapies. This could be due to physicians' medicalised understandings of the illness, despite research showing that doctors do recognise the influence of social factors in depression (McPherson & Armstrong, 2012).…”
Section: Depression Treatmentmentioning
confidence: 99%